2015
DOI: 10.1002/2015jf003474
|View full text |Cite
|
Sign up to set email alerts
|

Is it appropriate to model turbidity currents with the three‐equation model?

Abstract: The three-equation model (TEM) was developed in the 1980s to model turbidity currents (TCs) and has been widely used ever since. However, its physical justification was questioned because self-accelerating TCs simulated with the steady TEM seemed to violate the turbulent kinetic energy balance. This violation was considered as a result of very strong sediment erosion that consumes more turbulent kinetic energy than is produced. To confine bed erosion and thus remedy this issue, the four-equation model (FEM) wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…[]. The present three‐equation model does not fail in predicting turbidity currents from ignition point and, in turn, does not violate the four‐equation TKE balance [ Hu et al ., ]. Besides, in view of the self‐preserving type of velocity and concentration laws that are validated by the experimental data and used to develop the gradually varied flow relationships, perhaps a more than a qualitative rationality can be claimed for the computed results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[]. The present three‐equation model does not fail in predicting turbidity currents from ignition point and, in turn, does not violate the four‐equation TKE balance [ Hu et al ., ]. Besides, in view of the self‐preserving type of velocity and concentration laws that are validated by the experimental data and used to develop the gradually varied flow relationships, perhaps a more than a qualitative rationality can be claimed for the computed results.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hu et al . [] found that the three‐equation model does not fail to simulate self‐accelerating turbidity currents, rendering unclear the need of using the four‐equation model. Felix [] proposed a two‐dimensional turbulence model to address the development of turbidity current.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A turbidity current is a type of subaqueous sediment-laden gravity current [1][2][3][4], which has been studied using both a lock-exchange configuration (i.e., fixed volume) and a continuous-flux configuration. This study focuses on lock-exchange depositional turbidity currents, which represent those triggered by abrupt landslides and short-lived floods [5].…”
Section: Introductionmentioning
confidence: 99%
“…For those experimental studies within the lock-exchange configuration, most results [7,8,14] are presented in the form of the bulk values, i.e., the duration-averaged entrainment ratio. Hallworth et al [15] determined an average entrainment ratio of the lock-exchange gravity current on a flat bed as 0.063 ± 0.003. , 3 in which the entrainment ratio is defined as the ratio of the volumes of ambient and original fluid in the head. Recently, both the experimental and large eddy simulation results [16][17][18] indicate that the entrainment ratio of a lock-exchange gravity current is closely related to the initial density difference and the aspect ratio of the initial water depth to the lock length.…”
Section: Introductionmentioning
confidence: 99%